Constraints Facing Incremental Housing Construction in Dar es Salaam, Tanzania - Mselle , Justine; Sanga, Samwel Alananga (Penerbit Universiti Sains Malaysia, 2018)
The owner-built incremental housing strategy has been used for many years across the developing world. This study examines the implication of construction constraints and challenges on annual construction cost expenditure across housing types. Using descriptive statistics and correlation analysis for 43 incrementally built housing units implemented in Dar es Salaam between year 1993 and 2013, the study has observed that single and two-storey incremental housing builders face the same set of human related construction challenges and external cost-push factors but different administrative, physical and interest related constraints. Of all the cost-push factors examined, interest rate intervention is the only observed strategy that has far reaching potentials to single-storey low cost incremental builders because such builders are less likely to resort to loans as a mechanism to fnance housing. These fndings suggest that any other external efforts targeting physical or human related incremental construction constraints are likely to end up either benefting the high quality builders or every incremental builder regardless of cost or property type or both. The study argues in favour of targeted interest rate support rather than physical or administrative housing assistance if owner-builders are to beneft specifcally in any housing policy support.